Penerapan Nilai-Nilai Pendidikan Islam Holistik berbasis Karakter di Pondok Pesantren Miftahul Huda Al Azhar Citangkolo Kota Banjar di Era Revolusi Industri 4.0 - Ahyani, Hisam; Putra, Haris Maiza; Mutmainah, Naeli; Syamsudin, Syamsudin (Tarbawiyah Jurnal Ilmiah Pendidikan, 2023)
This paper narrates the failure of character education (morals) in Islamic boarding schools. In the midst of globalization and the era of the industrial revolution, students are required to take part in advancing civilization in the changing times. Responding to this challenge, Miftahul Huda Islamic Boarding School (PPMH) has developed an educational model through the application of character-based holistic Islamic educational values. Through this model, students are expected to have personality, master knowledge, and noble character in accordance with religious values. This study uses descriptive research methods and a field approach, where the primary sources are obtained from observation, interviews, and documentation. The results showed: 1) The application of character-based holistic Islamic education values ​​in PPMH was carried out through the inculcation of Holistic Islamic education values ​​from an early age, namely through: a) study of the yellow book, b) Santri independence, c) Santri obedience, d) Santri's respect, e) Santri's responsibility, f) Santri's honesty, g) Santri's tolerance, h) Santri's discipline, i) Santri's mutual cooperation, j) Santri's concern, k) Santri's cooperation, l) Santri's courage, and m) democracy; 2) The relevance of instilling the values ​​of character-based holistic Islamic education in PPMH can be used as a medium in the context of preventing santri radicalism. This application is carried out through the integration of the pesantren curriculum by studying classical books in the context of tafaqquh fiddiin, and trying to realize it in the form of daily practice with habituation and practice accompanied by exemplary examples from teachers, ustadz, or kiai.